The science of sound recording - Kadis, Jay (Focal Press/Elsevier, 2012)
The Science of Sound Recording will provide you with more than just an introduction to sound and recording, it will allow you to dive right into some of the technical areas that often appear overwhelming to anyone without an electrical engineering or physics background. The Science of Sound Recording helps you build a basic foundation of scientific principles, explaining how recording really works. Packed with valuable must know information, illustrations and examples of 'worked through' equations this book introduces the theory behind sound recording practices in a logical and practical way while placing an emphasis on the concepts of measurement as they relate to sound recording, physical principles of mechanics and acoustics, biophysics of hearing, introduction to electronics, analog and digital recording theory and how science determines mixing techniques.